2022
DOI: 10.1111/all.15584
|View full text |Cite
|
Sign up to set email alerts
|

KITD816V mutation in blood for the diagnostic screening of systemic mastocytosis and mast cell activation syndromes

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…67 Besides, detection of the KIT D816V mutation in hematopoietic cell compartments other than MC (multilineage involvement) has been associated with higher rate of progression from ISM to AdvSM and a worse outcome. 70,71 In line with this data, a value greater than 6% of circulating KIT D816V1 cells has been proposed as being suggestive of a multilineage involvement in patients. 68 Thus, the KIT D816V mutation burden seems to be a reliable and reproducible prognostic marker of SM, 5,67,72 now incorporated into prognostic scoring systems, such as the REMA score.…”
Section: Quantification Of the Kit D816v Mutational Burden For Progno...mentioning
confidence: 69%
“…67 Besides, detection of the KIT D816V mutation in hematopoietic cell compartments other than MC (multilineage involvement) has been associated with higher rate of progression from ISM to AdvSM and a worse outcome. 70,71 In line with this data, a value greater than 6% of circulating KIT D816V1 cells has been proposed as being suggestive of a multilineage involvement in patients. 68 Thus, the KIT D816V mutation burden seems to be a reliable and reproducible prognostic marker of SM, 5,67,72 now incorporated into prognostic scoring systems, such as the REMA score.…”
Section: Quantification Of the Kit D816v Mutational Burden For Progno...mentioning
confidence: 69%
“…Although the association between cMCD and severe HVA has been known for years, recent studies employing peripheral blood KIT p.D816V screening have only highlighted the true extent of this clinical association and further revealed that cMCD is often present in patients with normal BST levels [11,12,[26][27][28]. A recent study confirmed a high correlation between blood and bone marrow KIT p.D816V allele burden, demonstrating that the presence of KIT p.D816V in peripheral blood, which is a minor criterion for an SM diagnosis, was highly specific for cMCD, mostly (indolent) systemic mastocytosis ((I)SM), bone marrow mastocytosis (BMM) or monoclonal mast cell activation syndrome (c-MCAS) [29]. cMCD is a rare, largely underrecognized disease because it often reveals itself as secondary to another condition, typically anaphylaxis [13,17].…”
Section: Discussionmentioning
confidence: 93%
“…• Mastocitosis cutánea (CM): se caracteriza por la presencia de lesiones localizadas o diseminadas, marrones o rojas y con signo de Darier positivo (enrojecimiento al aplicar presión en una lesión), por la liberación de mediadores mastocitarios. (28) Subclasificación:…”
Section: Clasificaciónunclassified